Tooth Surface Design and Finite Element Analysis of Circular-arc Tooth Curvilinear Cylindrical Gear - Gao Xiaowei; Jia Jie; Yan Chang; Song Xuding (Jixie chuandong)
On the basis of the meshing theory of circular-arc tooth curvilinear cylinder gear,the corresponding design method and cutting theory are studied,and the tooth surface forming principle is analyzed.By using a double-sided cutter generating method and taking the cutting cone tooth surface which formed by cutter blade rotating as the imaginary tooth surface,the meshing process of the circular-arc tooth curvilinear cylindrical gear is simulated,the tooth surface equation is derived,the tooth surface numerical simulation is carried out and the visualization is realized.Then,the finite element mesh model is imported into ABAQUS software to carry out the finite element analysis,the contrastive analysis between the finite element analysis result and Hertz contact theory is carried out,and the result shows that built finite element model is reasonable.Through the comparison between the analysis results and the cylindrical gear with the same size,the result shows that the contact strength of circular-arc tooth curvilinear cylindrical gear is better than spur involute cylindrical gear.Beside,through the comparison analysis of the three groups size calculation examples of cutter radius,the relation between the cutter radius size and stress size is obtained.